Comparison of different harvest ways of Dendrobium officinale - Wang, Yang; Zhu, Yan; Si, Jin-Ping; Liu, Jing-Jing; Zhu, Yu-Qiu; Liu, Xiu-Juan (Zhongguo zhongyao zazhi, 2015)
To standardize the harvest ways of Dendrobium officinale and improve the quality and yield of D. officinale, a field experiment was carried out to study the effect of two kinds of harvest ways, which were keeping some of the axial shoot and harvesting all of the shoot by the end of the year. Then, the agronomic traits and yield were measured and the contents of polysaccharides and extractum were determined. The results showed that the harvest ways significantly affected the growth of D. officinale. Keeping some of the axial shoot could significantly improved the number of sprout, stem length, internode number and the internodal length, which also triggered increase the weight of fresh stems, leaves and the total of them and dry stems in per unit area, but it could not promote the stem diameter and the polysaccharide content in stems. Keeping some of the axial shoot moderately was conducive to the improvement of the production of medicinal materials in the process of harvesting by promoting the germination and growth of new buds, and to ensure the polysaccharide content by regulating the illumination and the density of cultivation.